Evaluation of Entrepreneurial Risk Level as Social Process in the Russian Economy - Pinkovetskaia, Iuliia; Gubernatorova, Elina; Kiseleva, Olga (Journal of History Culture and Art Research, 2019)
Development of the entrepreneurial sector requires information on the current risk levels in economy. The paper deals with three levels of entrepreneurial risk: acceptable, critical and catastrophic. The research aim is to assess the values of entrepreneurial risk that has been existing in recent years in aggregates of small and medium enterprises, formed by size and industry characteristics. Risk evaluation was made on the base of official statistics, characterize activity of all medium enterprises, small enterprises and microenterprises situated in Russia in 2015 and 2016. The paper presents the results of risk assessment for a set of medium enterprises, small enterprises and microenterprises in the Russian economy. From the results of the study it has been concluded that there is a significant differentiation of entrepreneurial risk levels by the types of economic activity. The industries with the maximum and minimum values of the existing entrepreneurial risks have been determined. The research outcomes can be used by entrepreneurs including beginners; federal, regional and municipal departments' authorities related to the regulation of entrepreneurial activity; financial and credit, insurance, leasing organizations.